A Rare Abdominal Tumour in a Paediatric Age Group: Pheochromocytoma - Sah, Rajesh Prasad; Sah, R.G.; Mahmood, Shaukat (Journal of Nepal Paediatric Society, 2017)
A 10 year boy presented with history of abdominal pain and palpitation. Abdominal ultrasound and CT oriented towards the diagnosis. After preoperative optimization, laparotomy with complete excision of an unusual pheochromocytoma tumour of about 8×10 cm adherent to liver and IVC performed. Histopathology confirmed the diagnosis without evidence of malignancy.